2020
DOI: 10.1111/ecog.05251
|View full text |Cite
|
Sign up to set email alerts
|

Artificial nightlight alters the predator–prey dynamics of an apex carnivore

Abstract: Artificial nightlight is increasingly recognized as an important environmental disturbance that influences the habitats and fitness of numerous species. However, its effects on wide‐ranging vertebrates and their interactions remain unclear. Light pollution has the potential to amplify land‐use change, and as such, answering the question of how this sensory stimulant affects behavior and habitat use of species valued for their ecological roles and economic impacts is critical for conservation and land‐use plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 73 publications
1
54
0
Order By: Relevance
“…At the scale of ecological communities, significant insights remain to be gained about predator-prey relationships, pollinator-plant relationships, and other ecological interactions. For example, recent research has demonstrated the influence of light at night at a coarse scale on mountain lion predation on mule deer [45]. Because irradiance from ALAN can vary orders of magnitude within several hundred meters [46], higherresolution data are needed to sort the influence of ALAN on many existing datasets containing ecological information.…”
Section: Ecologymentioning
confidence: 99%
“…At the scale of ecological communities, significant insights remain to be gained about predator-prey relationships, pollinator-plant relationships, and other ecological interactions. For example, recent research has demonstrated the influence of light at night at a coarse scale on mountain lion predation on mule deer [45]. Because irradiance from ALAN can vary orders of magnitude within several hundred meters [46], higherresolution data are needed to sort the influence of ALAN on many existing datasets containing ecological information.…”
Section: Ecologymentioning
confidence: 99%
“…1, 2 ). General consensus among experts points to sensitivity among nocturnal species that alter behavior in response to variation in artificial and natural light levels (Ditmer et al 2020a, Willems et al 2020, Prugh and Golden 2014), plus nocturnal acoustic specialists that respond negatively to noise exposure (Senzaki et al 2016). Although the expert concordance was relatively high, it is possible that this general consensus may reflect sparse evidence among diurnal species, rather than an absence of effects.…”
Section: Discussionmentioning
confidence: 99%
“…Both can fundamentally alter spatial orientation and create mismatched biological timings (Gaston et al 2017). These sensory disturbances in turn create a myriad of behavioral alterations, affecting orientation and movement (Slabbekoorn & Bouton 2008; Cabrera-Cruz, Smolinsky, & Buler 2018), communication (Francis & Barber 2013), foraging and hunting efficiency (Bennie et al 2015; Bunkley & Barber 2015; Mason, McClure, & Barber 2016), altered energy budgets (Read et al 2014; Touzot et al 2019) and predation risk (Francis & Barber 2013; Ditmer et al 2020a), along with increased physiological stress (Rolland et al 2012; Ouyang, Davies, & Dominoni 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Adding jaguars could alter the “landscape of fear” (Gaynor, Brown, Middleton, Power, & Brashares, 2019; though see Hoskinson, 2018). The best strategy for deer to avoid a nocturnal ambush predator such as the jaguar is to avoid thick and dark cover at night (Ditmer et al, 2020; Gehr et al, 2017), forcing deer into more open areas, where human hunters are more successful (Lone et al, 2014). In Europe, restoring the Eurasian lynx ( Lynx lynx ) facilitated greater human hunting success for roe deer ( Capreolus capreolus ; Gehr et al, 2018).…”
Section: The Case For Reintroductionmentioning
confidence: 99%